Metastatic feline mammary cancer: prognostic factors, outcome and comparison of different treatment modalities – a retrospective multicentre study. Issue 6 (June 2021) - Petrucci, Gonçalo; Henriques, Joaquim; Gregório, Hugo; Vicente, Gonçalo; Prada, Justina; Pires, Isabel; Lobo, Luís; Medeiros, Rui; Queiroga, Felisbina
Objectives: Although feline mammary carcinomas (FMCs) are highly metastatic, the literature and treatment options pertaining to advanced tumours are scarce. This study aimed to investigate the clinical outcome of metastatic FMC with or without adjuvant treatment. Methods: The medical records of 73 cats with metastatic FMC (stage IV) were reviewed and included in this study. Metastatic disease was detected by distinct imaging techniques (radiography, ultrasound and CT) and confirmed by cytology and/or histopathology. Cats with adjuvant chemotherapy treatment (n = 34) were divided into three groups: group 1 (n = 9) cats receiving maximum tolerated dose chemotherapy; group 2 (n = 15) cats receiving metronomic chemotherapy; and group 3 (n = 10) cats treated with toceranib phosphate. The study endpoints were time to progression (TTP) and tumour-specific survival (TSS). Treatment-related toxicity was evaluated according to the Veterinary Co-operative Oncology Group's Common Terminology Criteria for Adverse Events version 1.1 (VCOG-CTCAE). Results: Overall mean TTP and TSS were 23 and 44 days, respectively. Cats with clinical signs at the time of diagnosis had a lower TSS (14 days) than asymptomatic cats (128 days; P <0.001). Cats with pleural effusion had a lower TSS (16 days) than cats without ( P <0.001). Median TSS was 58, 75 and 63 days in groups 1, 2 and 3, respectively ( P = 0.197). Toxicity was observed in 66.7%, 20% and 30% of cats in groups 1, 2 and 3, respectively. Conclusions and relevance: To the best of our knowledge, this study includes the highest number of patients with metastatic FMC assessed. Despite the overall poor prognosis, some cats survived >6 months, indicating that adjuvant treatment may be an option to consider in metastatic disease. More studies are warranted for better understanding and management of stage IV patients.